FAKTOR-FAKTOR YANG MEMENGARUHI MOTIVASI BEROBAT PENDERITA TUBERKULOSIS DI KOTA PEKALONGAN TAHUN 2012 - Sutarno, -; Utama, Gilang Alip (Jurnal Ilmiah Widya, 2013)
Tuberculosis (TB) is one of contagious diseases that are still being a major problem in the world especially in developing countries. Indonesia ranks fifth as the country with the world's highest TB burden in 2009. Based on these conditions it is required a serious effort to mobilize the community to consult and seek medical service of the disease. This research’s aims to examine the influence of social support, knowledge, and perceptions of treatment motivation of TB patients in Pekalongan city as a region which have been able to achieve the target of tuberculosis cases very well. The data used a primary data with a single-stage cluster sampling as the sampling technique where the determination of cluster unit (health centers) used a systematic linear. The analysis method is descriptive analysis and path analysis. The results of research show that social support, knowledge, and perceptions of TB has positive significantly effect on motivation for treatment. Social support from family and tuberculosis officers is variables that have the greatest influence on motivation for treatment. Therefore, the patient's family together with TB officers should always provide help to the patient during the period intensive treatment.